Construction of the Virtual Embodiment Questionnaire (VEQ) - Roth, Daniel; Latoschik, Marc Erich (IEEE Transactions on Visualization and Computer Graphics, 2020)
User embodiment is important for many virtual reality (VR) applications, for example, in the context of social interaction, therapy, training, or entertainment. However, there is no data-driven and validated instrument to empirically measure the perceptual aspects of embodiment, necessary to reliably evaluate this important phenomenon. To provide a method to assess components of virtual embodiment in a reliable and consistent fashion, we constructed a Virtual Embodiment Questionnaire (VEQ). We reviewed previous literature to identify applicable constructs and questionnaire items, and performed a confirmatory factor analysis (CFA) on the data from three experiments (N=196). The analysis confirmed three factors: (1) ownership of a virtual body, (2) agency over a virtual body, and (3) the perceived change in the body schema. A fourth study (N=22) was conducted to confirm the reliability and validity of the scale, by investigating the impacts of latency and latency jitter present in the simulation. We present the proposed scale and study results and discuss resulting implications.
CRIS-Team Scopus Importer:2021-03-29
Keywords: Agency; Avatars; Body Ownership; Virtual Embodiment; Virtual Reality